Penile fracture with urethral injury: a case report of rare double trouble - Farooq Hameed; Adeel Anwaar; Humayun Saeed; Usman Noor; Abdullah Saleem; Mamoona Anwar (Bulletin of the National Research Centre, 2023)
Abstract Background A penile fracture occurs when the tunica albuginea of penis tears during erection. Penile fracture is a rare but serious injury that occurs when the erect penis sustains a traumatic force. It is characterized by a sudden snapping or popping sound, followed by immediate pain, swelling, and discoloration. Its association with concomitant urethral injury is very rare. This case study describes such a rare case. Case presentation In this case study, we present the case of a 47-year-old man who experienced sudden pain and lost erection with a popping sound while having sexual intercourse. There was bloody discharge from the urethral opening and showed the distinct sign of an "Eggplant Deformity." This result confirmed the diagnosis. Immediate surgical intervention revealed damage to the left corpora and urethra. The procedure involved repairing the tunica albuginea covering the corpora tissue and reconstructing the damaged urethra. The surgery went smoothly without complications. The patient reported satisfactory erectile function and normal urination on follow-up visit after 2 months. Conclusion Penile fracture with urethral injury is a rare but serious emergency. Prompt detection and surgical intervention are crucial for optimal outcomes and minimal complications. Depending on severity, either catheterization or repair may be necessary.